(untitled) (Stavební obzor - Civil Engineering Journal, 2024)
During the construction process of shield tunneling with ultra-large diameter under normal and pressurized conditions, problems such as mud cake formation on the cutterhead, stagnation of mud in the chamber, blockage of slurry discharge chute, high cutterhead torque, and slow excavation speed are prone to occur. In severe cases, these issues can impact construction progress and pose a threat to construction safety. Taking the Guangzhou Haizhu Bay Tunnel project as a case study, this paper proposes prevention and drainage technology for anti-stuck and discharging during shield tunneling in complex red rock strata with ultra-large diameter under normal and pressurized conditions, focusing on mud slurry control, optimization of cutterhead flushing system, excavation parameter control, and cutter tool optimization.